Stress fractures of the foot and ankle. Issue 8 (August 2017) - Welck, M.J.; Hayes, T.; Pastides, P.; Khan, W.; Rudge, B.
Abstract: Stress fractures occur as a result of microscopic injuries sustained when bone is subjected to repeated submaximal stresses. Overtime, with repeated cycles of loading, accumulation of such injuries can lead to macro-structural failure and frank fracture. There are numerous stress fractures about the foot and ankle of which a trauma and orthopaedic surgeon should be aware. These include: metatarsal, tibia, calcaneus, navicular, fibula, talus, medial malleolus, sesamoid, cuneiform and cuboid. Awareness of these fractures is important as the diagnosis is frequently missed and appropriate treatment delayed. Late identification can be associated with protracted pain and disability, and may predispose to non-union and therefore necessitate operative intervention. This article outlines the epidemiology and risk factors, aetiology, presentation and management of the range of stress fractures in the foot and ankle.